(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Adhatoda vasica Nees., also known as Malabar nut or Vasa, has long been utilized in traditional medicine for its potent respiratory therapeutic properties. This plant has been used for 2000 years to treat respiratory problems. The leaves of this plant give a stimulant effect on the respiratory system. In Ayurveda medicinal system it is considered a potent herb to cure diseases like cough, symptoms of cold, asthma, bronchitis. Vasa is said to have Tikta and Katu in Rasa and Sheet in Veerya it has Katu Vipaka and is said to have Kapha-Pittahara property. Vasa was reviewed in various text like Veda, Samhita, Kosha Grantha. Vasa was found to be as the main ingredient of many formulations in the treatment of Raktpitta, Kaphaj Vikar, Vataj Vikar, and other respiratory diseases. Vasa Swarasa was found in various formulations used as Bhawana Dravya, also various Paryaya, Guna, Karma and different opinions of Acharyas in various Samhitas were observed.